Investigating the Effectiveness of Transactional Analysis (TA) Training on the Mental Health of Female Middle School Students - Shirali Kharamin, Salam; Moradian, Mahboubeh (KMAN Counseling & Psychology Nexus, 2023)
This study aimed to investigate the effectiveness of Transactional Analysis (TA) training on the mental health of female middle school students in Yasuj city. A quasi-experimental design with pretest-posttest control groups was utilized. The sample consisted of 50 female students selected based on their General Health Questionnaire scores and randomly assigned to either the experimental or control group. TA training was delivered over 9 weeks, with assessments conducted before and after the intervention. The experimental group showed significant improvements in mental health scores post-intervention (M = 31.72, SD = 13.81) compared to the control group (M = 28.96, SD = 10.23), with an F value of 20.91 indicating the effectiveness of TA training at p < 0.01. TA training significantly enhances the mental health of female middle school students, suggesting its potential as a valuable tool in educational settings for promoting psychological well-being.